2016
DOI: 10.1038/srep35100
|View full text |Cite
|
Sign up to set email alerts
|

Translation Elongation Factor eEF1A2 is a Novel Anticancer Target for the Marine Natural Product Plitidepsin

Abstract: eEF1A2 is one of the isoforms of the alpha subunit of the eukaryotic Elongation Factor 1. It is overexpressed in human tumors and is endowed with oncogenic properties, favoring tumor cell proliferation while inhibiting apoptosis. We demonstrate that plitidepsin, an antitumor agent of marine origin that has successfully completed a phase-III clinical trial for multiple myeloma, exerts its antitumor activity by targeting eEF1A2. The drug interacts with eEF1A2 with a KD of 80 nM and a target residence time of cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 44 publications
1
95
0
Order By: Relevance
“…eEF1A1 is reported to be a negative regulator p53 and p73 and leading to chemoresistance (Blanch et al 2013), and the ubiquitin-like protein FAT10 has been shown to bind eEF1A1 which stabilizes the expression of eEF1A1 in favor of tumor cell proliferation (Liu et al 2016). The isoform eEF1A1 shares 96% homology with the isoform eEF1A2, the primary target of plitidepsin (dehydrodidemnin B/Aplidin, PharmaMar), an antitumor agent of marine origin (Losada et al 2016). eEF1A isoforms were the only proteins detected as capable of binding plitidepsin, and sensitivity was dependent on eEF1A2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…eEF1A1 is reported to be a negative regulator p53 and p73 and leading to chemoresistance (Blanch et al 2013), and the ubiquitin-like protein FAT10 has been shown to bind eEF1A1 which stabilizes the expression of eEF1A1 in favor of tumor cell proliferation (Liu et al 2016). The isoform eEF1A1 shares 96% homology with the isoform eEF1A2, the primary target of plitidepsin (dehydrodidemnin B/Aplidin, PharmaMar), an antitumor agent of marine origin (Losada et al 2016). eEF1A isoforms were the only proteins detected as capable of binding plitidepsin, and sensitivity was dependent on eEF1A2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Such interaction inhibits the pro-oncogenic behavior of eEF1A2. Interestingly, eEF1A2 is overexpressed in many malignancies, including multiple myeloma (MM) [145]. In vitro studies showed that Plitidepsin elicits strong cytotoxic activity in several cancer cell lines, presenting IC 50 values ≤1 nM [146], and in vivo studies demonstrated the potent antiproliferative effects of Plitidepsin in xenograft models of MM [147].…”
Section: Marine Compounds Approved For Cancer Treatmentmentioning
confidence: 99%
“…Binding of plitidepsin (i.e. dehydrodidemnin B) to this same site in the closely related eEF1A2 is believed to stabilize the "active" conformation of eEF1A2 (Losada, et al, 2016), perhaps by preventing dimer formation. (Sánchez-Murcia, Cortés-Cabrera and Gago, 2017).…”
Section: Eef1a As a Natural Product Drug Target In Cancer Therapymentioning
confidence: 99%
“…Despite the training in the purification of this protein from its natural source, this step was optimized and routinely executed at PharmaMar's facilities. The protocol followed for extraction and purification of eEF1A2 is reported by Losada, A. et al (2016).…”
Section: Protein Purification From Natural Sources (Eef1a2)mentioning
confidence: 99%
See 1 more Smart Citation